THE ROLE OF LOCAL WISDOM IN THE MANAGEMENT OF VILLAGE TOURISM IN NAGARI SUMPUR, BATIPUH SELATAN DISTRICT, TANAH DATAR REGENCY, WEST SUMATRA PROVINCE - Muhammad Najmul Fahmi; Nazwa Aulia Azhari; M. Hayqal Adibya; Elfayetti Elfayetti (USN Kolaka, 2025)
Nagari Sumpur is a local tourism village that still has Minangkabau cultural heritage. However, the main challenge is the lack of participation of the younger generation in preserving customs and the need for a balance between modernization and preservation of tradition in tourism management. This commitment is intended to determine the potential of local wisdom that can be integrated into sustainable tourism and culture-based management strategies. This study uses a qualitative method with a descriptive approach that includes direct observation, interviews with traditional managers, tourism managers, communities, tourists, and data analysis related to the sustainability of cultural tourism. The results of the commitment indicate that traditions such as Landai, traditional Silat and makan bajamba can be packaged as part of a tourism program to increase attraction and at the same time maintain cultural identity. With the right strategy, Nagari Sumpur can develop as a model for sustainable local wisdom-based tourism villages.